2018
DOI: 10.1155/2018/1419369
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Submucosal Tunnel Dissection for Large Gastric Neoplastic Lesions: A Case-Matched Controlled Study

Abstract: Aim To evaluate the efficacy and safety of endoscopic submucosal tunnel dissection (ESTD) for resection of large superficial gastric lesions (SGLs). Methods The clinicopathological records of patients performed with ESTD or endoscopic submucosal dissection (ESD) for SGLs between January 2012 and January 2014 were retrospectively reviewed. 7 cases undergoing ESTD were enrolled to form the ESTD group. The cases were individually matched at a 1 : 1 ratio to other patients performed with ESD according to lesion lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…A total of 22 studies were further excluded for the following reasons: (a) insufficient data; (b) duplicates; (c) irrelevant to the review topic; (d) studies on animal models; and (e) case reports and review articles. Seven studies 7‐13 were finally inclued for this meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 22 studies were further excluded for the following reasons: (a) insufficient data; (b) duplicates; (c) irrelevant to the review topic; (d) studies on animal models; and (e) case reports and review articles. Seven studies 7‐13 were finally inclued for this meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 2, two studies that reported recurrence, 9,12 including one in the ESTD group and two in the ESD group. One recurrence of poorly‐to‐moderately differentiated intramucosal adenocarcinoma was found in the ESTD group at 15 months of follow‐up.…”
Section: Resultsmentioning
confidence: 99%
“…As the population ages, endoscopists are increasingly faced with challenges associated with treating older patients with comorbidities safely and effectively [16, 17]. Currently, ESD is widespread as a minimally invasive endoscopic treatment for early gastrointestinal cancer and is also actively applied to large lesions and lesions with an ulcer scar that cannot be resected using conventional endoscopic mucosal resection (EMR) [18–20]. ESD requires precise and complicated maneuvers and, thus, results in longer operating times and increases the risks of undesirable side effects compared with EMR.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of endoscopic submucosal tunnel dissection (ESTD) has been reported as a good method for providing traction. 1,2 However, ESTD alone did not provide enough traction in this case because of the lesion size and extensive severe fibrosis. In such a situation, combined use of traction by using ring-thread counter traction was effective (Fig.…”
mentioning
confidence: 80%